PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity - Jessica van Setten (Nature Portfolio, 2018)
Abnormal PR interval duration is associated with risk for atrial fibrillation and heart block. Here, van Setten et al. identify 44 PR interval loci in a genome-wide association study of over 92,000 individuals and find genetic overlap with QRS duration, heart rate and atrial fibrillation.